2006
DOI: 10.1126/science.1130276
|View full text |Cite
|
Sign up to set email alerts
|

S6K1- and ßTRCP-Mediated Degradation of PDCD4 Promotes Protein Translation and Cell Growth

Abstract: The tumor suppressor programmed cell death protein 4 (PDCD4) inhibits the translation initiation factor eIF4A, an RNA helicase that catalyzes the unwinding of secondary structure at the 5' untranslated region (5'UTR) of messenger RNAs (mRNAs). In response to mitogens, PDCD4 was rapidly phosphorylated on Ser67 by the protein kinase S6K1 and subsequently degraded via the ubiquitin ligase SCF(betaTRCP). Expression in cultured cells of a stable PDCD4 mutant that is unable to bind betaTRCP inhibited translation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
579
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 641 publications
(621 citation statements)
references
References 15 publications
36
579
2
4
Order By: Relevance
“…As for PTEN, the RAS-dependent downregulation of PDCD4 is predominantly mediated by miR-21. It has been reported that PDCD4 expression is controlled by ubiquitylation and proteasomal degradation triggered by S6K1-phosphorylation, during cell cycle re-entry (Dorrello et al, 2006). This rapid control mechanism is not implicated in the RAS-dependent downregulation of PDCD4, in which the decrease of PDCD4 parallels the slow induction of miR-21 (Figure 3) and is relieved by the miR-21 knockdown ( Figure 6).…”
Section: Discussionmentioning
confidence: 90%
“…As for PTEN, the RAS-dependent downregulation of PDCD4 is predominantly mediated by miR-21. It has been reported that PDCD4 expression is controlled by ubiquitylation and proteasomal degradation triggered by S6K1-phosphorylation, during cell cycle re-entry (Dorrello et al, 2006). This rapid control mechanism is not implicated in the RAS-dependent downregulation of PDCD4, in which the decrease of PDCD4 parallels the slow induction of miR-21 (Figure 3) and is relieved by the miR-21 knockdown ( Figure 6).…”
Section: Discussionmentioning
confidence: 90%
“…In vitro ubiquitylation assay was performed using proteins translated in a reticulocyte system, as previously done for SCF βTrcp (Dorrello et al , 2006). Myc‐tagged Fbxl17 (318–701) and Sufu WT or Sufu K257R were in vitro translated using TnT Quick Coupled Transcription/Translation System reticulocyte system from Promega according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The phosphatidylinositol 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) signaling pathway has been shown to induce the proteolysis of PDCD4 [31] and reduce the transcription of PDCD4 [32]. MicroRNA-21 has been reported to block PDCD4 expression transcriptionally [33] and post-transcriptionally [34].…”
Section: Pdcd4 Increases Timp-2 Expression To Inhibit Breast Cancer Imentioning
confidence: 99%